The biochemical and morphostructural features of biological fluids in patients with rapidly growing uterine myoma - E. G. Shvarev; L. V. Dikareva; A. K. Ayupova; G. E. Shvarev (Опухоли женской репродуктивной системы, 2014)
The paper analyzes and presents the clinical and laboratory data of 978 female patients, including 268 (27.4%) control women having no reproductive organ tumors, 478 (48.8%) and 232 (23.7%) patients with slowly and rapidly growing uterine myoma (UM), respec- tively. A new procedure has been developed and tested to diagnose rapidly growing UM, including the latter concurrent with endometrial hyperplastic processes, which is based on the comparison of the levels of lipid peroxidation products in the biomolecules in the study biological fluids (endometrial lavages) and on the analysis of their morphostructural features. A mathematical model to calculate uterine volume has been proposed to objectify the estimation of tumor growth rates. The proposed multimodal approach makes it possible to detect UM, to determine its growth rate and endometrial status, and to assess the likelihood of a recurrence occurring after conservative surgery.